2014
DOI: 10.15347/wjm/2014.001
|View full text |Cite
|
Sign up to set email alerts
|

Reference ranges for estradiol, progesterone, luteinizing hormone and follicle-stimulating hormone during the menstrual cycle

Abstract: This is a description for a series of diagrams showing the reference ranges for the blood content of the hormones estradiol (the main estrogen), progesterone, follicle-stimulating hormone and luteinizing hormone during the menstrual cycle, as established on a reference group in Switzerland using the Abbott ARCHITECT analyzer. InterpretationThe time scale starts with the beginning (or "onset") of (last) menstrual period (LMP), given as day number. Day number 1 corresponds to 0 to 0.99 days from the beginning of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 8 publications
1
22
1
Order By: Relevance
“…The present study has shown that there is a tendency for CRDs and DBs to be present in the luteal phase of the menstrual cycle and this supports our previous work . The luteal phase is characterised by higher levels of progesterone and oestradiol than in the early follicular phase . However, in our present female subjects there was no clear relationship between the blood hormone levels and presence or absence of CRDs/DBs.…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…The present study has shown that there is a tendency for CRDs and DBs to be present in the luteal phase of the menstrual cycle and this supports our previous work . The luteal phase is characterised by higher levels of progesterone and oestradiol than in the early follicular phase . However, in our present female subjects there was no clear relationship between the blood hormone levels and presence or absence of CRDs/DBs.…”
Section: Discussioncontrasting
confidence: 76%
“…). Three of the women had CRDs and DBs in both the early follicular and luteal phases of the menstrual cycle (Figs and ). A further five women had normal sphincter EMG in the early follicular phase and CRDs and DBs in the mid‐luteal phase (Figs and ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…16 The ability to detect a significant BOLD response appears to vary with menstrual cycle changes. In general, a larger BOLD response was observed in the menstrual and luteal phases of the cycle when estrogen levels tend to be lower 23 ; however, further work is needed to confirm this hypothesis. Differences in breast morphology and composition between subjects may be a further source of intersubject variation in response.…”
Section: Discussionmentioning
confidence: 96%
“…These groups were chosen as estrogen levels are at their highest between days 10 and 20, taking into account variations in ovulation and cycle length. 23 A Student's t-test was used to compare the GAR during two different phases of the menstrual cycle. All analyses were performed using R v. 3.1.3 (R Foundation for Statistical Computing, Vienna, Austria).…”
Section: Discussionmentioning
confidence: 99%